A Study on the Employment Support Service System for Visually Impaired College Students in China - Bo, Zhou; Hock, Kway Eng (South Asian Journal of Social Sciences and Humanities, 2024)
At present, the problem of difficult employment for disabled college students in China is  becoming more and more prominent, and the construction of an employment support service  system for colleges and universities is one of the most important means of alleviating the  employment pressure on disabled college students and promoting the healthy development of  society. Based on the perspectives of visually impaired college students and colleges and  universities, this study adopts qualitative research methods such as interview method and  observation method, selects 10 visually impaired students from a college in China as the  research object, and statistically analyses the raw data of the interviews with NVivo data  analysis tools, and builds a college employment support service system with the core of  education and training and support, employment guidance and consulting, social resources  integration and enhancing social and enterprise inclusiveness. The service system is of great  practical significance for promoting high-quality employment and better integration of  visually impaired students into society, as well as creating a harmonious and inclusive  employment support environment.
Keywords: Visually Impaired College Students; Employment Support Service System; Colleges and Universities